Plato (428 BCE-347 BCE) - Arnold, Thomas; Halfwassen, Jens (International encyclopedia of the social & behavioral sciences, 2015)
Plato is one of the most influential figures in the development of European thought. This article provides a short biography, deals with the complexities of interpreting Plato, and covers the main areas of Platonic thought (ontology, epistemology, ethics, and politics) and the major Platonic doctrines (Dialectic, Theory of Forms, and Unwritten Doctrine).
Gesehen am 14.10.2020